Elaborar y aplicar un manual de actividades lúdicas matemáticas, para afianzar las habilidades lógico matemáticas en los niños y niñas de primer año de educación básica de la escuela fiscal mixta “Otto Arosemena Gómez” en el cantón Latacunga provincia de Cotopaxi en el año lectivo 2012-2013 - Masapanta Rivera, Mariela Alexandra (2015)
The ludic activities have been considered a basic element in the integral development of children, equal a vital need, pleasant and spontaneous. your application in education would be undeniable benefits for all, Thats why this job is focused on the game and use in any time process teaching and learning as an educational resource that offers great opportunities to hoped chital formation. The present research focuses on the importance of ludic activities in early childhood education. The general objective was determine how ludic activities affect learning of pre- math. The population in study was consisted for the head master, teachers and children of the Otto Arosemena Gomez School. In the research the qualitative and observation techniques and interviews was used. The research try on the elaboration and apply of a manual of ludic activities math in the children of first year of basic education fiscal mixed Otto Arosemena Gomez " school . it was required to develop this manual , because exist a great need by different teachers who teach the little ones, same that provide a lot of information that it is applied at teaching of math.